Enhancement of the antimicrobial properties of bacteriophage‐K via stabilization using oil‐in‐water nano‐emulsions. (14th April 2014) - Esteban, Patricia Perez; Alves, Diana R.; Enright, Mark C.; Bean, Jessica E.; Gaudion, Alison; Jenkins, A.T.A.; Young, Amber E.R.; Arnot, Tom C.
<x xml:space="preserve">Abstract</x> Bacteriophage therapy is a promising new treatment that may help overcome the threat posed by antibiotic‐resistant pathogenic bacteria, which are increasingly identified in hospitalized patients. The development of biocompatible and sustainable vehicles for incorporation of viable bacterial viruses into a wound dressing is a promising alternative. This article evaluates the antimicrobial efficacy of Bacteriophage K against Staphylococcus aureus over time, when stabilized and delivered via an oil‐in‐water nano‐emulsion. Nano‐emulsions were formulated via thermal phase inversion emulsification, and then bacterial growth was challenged with either native emulsion, or emulsion combined with Bacteriophage K. Bacteriophage infectivity, and the influence of storage time of the preparation, were assessed by turbidity measurements of bacterial samples. Newly prepared Bacteriophage K/nano‐emulsion formulations have greater antimicrobial activity than freely suspended bacteriophage. The phage‐loaded emulsions caused rapid and complete bacterial death of three different strains of S. aureus. The same effect was observed for preparations that were either stored at room temperature (18–20°C), or chilled at 4°C, for up to 10 days of storage. A response surface design of experiments was used to gain insight on the relative effects of the emulsion formulation on bacterial growth and phage lytic activity. More diluted emulsions had a less significant effect on bacterial growth, and diluted bacteriophage‐emulsion preparations yielded greater antibacterial activity. The enhancement of bacteriophage activity when delivered via nano‐emulsions is yet to be reported. This prompts further investigation into the use of these formulations for the development of novel anti‐microbial wound management strategies. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:932–944, 2014